Estudos biológicos e ecológicos da interação entre Nephila clavipes (Araneae, nephilidae) e o parasitoide Hymenoepimecis bicolor (Hymenoptera, Ichneumonidae, pimplinae) - Sobczak, Jober Fernando (2013)
Parasitoid wasps may use a wide variety of arthropods as food for their larvae. Among koinobiont species, whose development of the parasitoid does not disrupt the normal activities of the host, there is a group of wasps that exclusively uses spiders as hosts. In Polysphincta group (Hymenoptera, Ichneumonidae, Pimplinae), some species are able to change their hosts behavior before turning into pupa. These behavioral changes that are possibly responsible for an increase in the probability of survival of the parasitoid, are rare in this type of interaction. In this study, which was divided into four chapters, the interaction between the spider Nephila clavipes (Araneae, Nephilidae) and Hymenoepimecis bicolor wasp (Hymenoptera, Ichneumonidae, Pimplinae) are described in detail. In the first chapter we describe the attack and oviposition behavior of H. bicolor,that starts with the wasp flying around the N. clavipes web. Then the wasp attacks inserting the ovipositor into the mouth and paralyzing the spider at the center of the web. Females H. bicolor emerge from larger spiders while males emerge from smaller spiders. Apparently the wasp is able to estimate the size of the host and decide whether or not to fertilize the egg to be laid down in the spider. In the second chapter, we found the frequency of parasitism in N. clavipes for H. bicolor and also verify the choice of the host size, can be directly related to a trade-off between size and risk of injury. The ecdysis is not able to remove the parasitoid larva which remains attached to the spider body. Furthermore, we note that six days before the ecdysis, so in the period of pre-ecdysis, there is a decrease in the number of rays and turns, causing a decrease in the web size. The changed web built by spiders in the preecdysis is very similar to the modified web built by spiders parasitized days before being killed by the parasitoid larva. xi The third chapter describes the influence of the architecture of the modified webs and the normal ones on the survival of pupa of H. bicolor. In normal webs the pupa survival is greatly affected and in most of the observations cocoons fell in the soil or suffered other kind damage. In another experiment, we removed the third instar larva in the moment that the spider began to build the modified web and we found that after removing the larva the spider start building its standard web. Thus, our goal was to verify if that the larva injects substances that induce the spider to build a web modified. In the final chapter the immature stages of the H. bicolor are described by observing morphological and behavioral characteristics in each stage